The Organization of Teaching Material by the Higher School Teacher in his Professional Activity - O. M. Kolomiets (Сеченовский вестник)
The article is devoted to an actual problem of modern education – the organization of teaching activities that ensure mastery of each student’s educational outcomes, level of quality in accordance with the requirements of Federal state educational standards. The educational material on the orientation phase of the teaching activities in the preparation of training sessions is described. The article presents new types of didactic means: «scheme of orientation in the training material», «table of orientation in the subject», «map of orientation in the activities» improving the quality of student’s mastery of elements of knowledge in the structure of competences. The function, structure and content of these tools, the scientifi c methods of their construction by a teacher are described. The novelty of this work is to use the scientifi c principles of competence-activity approach to solving the problem of the study.